Reading Lionel Fogarty. Issue 6 (3rd June 2022) - Klee, Louis
ABSTRACT: Lionel Fogarty occupies a curious place in Australia letters. Widely regarded as the most important Aboriginal poet of his generation and even, as John Kinsella declares, 'the greatest living Australian poet', he has nevertheless received relatively little attention from scholars and is published by small, independent presses. Where considered at all, his politically charged, singular poetry is often treated with baffled awe or else conceived as a method of resisting the coloniser through an idiosyncratically 'creolised' English. This paper returns to various critical attempts to think Fogarty's poetry, from 'deep reading' to 're-reading' – some of which, like the trope of 'unsettlement', have yielded influential hermeneutics for the reading of Australian poetry per se – and treats these past readings as an entry point for an analysis of the complex rhetorical and poetic games of address in Fogarty's poetics. It considers, in turn, the poetic importance of Fogarty's sustained commitment to internationalist, liberationist, and anti-colonial politics, which it conceives as a poetics of solidarity.